Analisis Efektivitas Model Pembelajaran Problem Based Learning Dalam Pendidikan Vokasi Berbasis Meta-Analysis - Marta, Rizkayeni; Ambiyar; Wulansari, Rizky Ema; Yulianti, Rosi (The Indonesian Journal of Computer Science, 2024)
The Problem-Based Learning (PBL) model has become a major focus in vocational education, promising an integrated and contextual approach to problem-oriented learning. This research aims to conduct a meta-analysis of existing scientific publications to gain a deeper understanding of the effectiveness of the PBL model in vocational education. The results of the analysis indicate that the success of PBL implementation in vocational education is significantly influenced by several variables, including appropriate learning design, support from instructors/facilitators, and interactions among learners. With a deeper understanding of the factors affecting the effectiveness of PBL in vocational education, it is expected that this learning model can be improved and developed more optimally, thereby making a more significant contribution to enhancing learning outcomes, skills, and the readiness of learners to enter the workforceThe Problem-Based Learning (PBL) model has become a major focus in vocational education, promising an integrated and contextual approach to problem-oriented learning. This research aims to conduct a meta-analysis of existing scientific publications to gain a deeper understanding of the effectiveness of the PBL model in vocational education. The results of the analysis indicate that the success of PBL implementation in vocational education is significantly influenced by several variables, including appropriate learning design, support from instructors/facilitators, and interactions among learners. With a deeper understanding of the factors affecting the effectiveness of PBL in vocational education, it is expected that this learning model can be improved and developed more optimally, thereby making a more significant contribution to enhancing learning outcomes, skills, and the readiness of learners to enter the workforce